Learning anatomy enhances spatial ability. Issue 4 (24th January 2013) - Vorstenbosch, Marc A.T.M.; Klaassen, Tim P.F.M.; Donders, A.R.T. (Rogier); Kooloos, Jan G.M.; Bolhuis, Sanneke M.; Laan, Roland F.J.M.
Abstract : Spatial ability is an important factor in learning anatomy. Students with high scores on a mental rotation test (MRT) systematically score higher on anatomy examinations. This study aims to investigate if learning anatomy also oppositely improves the MRT‐score. Five hundred first year students of medicine ( n = 242, intervention) and educational sciences ( n = 258, control) participated in a pretest and posttest MRT, 1 month apart. During this month, the intervention group studied anatomy and the control group studied research methods for the social sciences. In the pretest, the intervention group scored 14.40 (SD: ± 3.37) and the control group 13.17 (SD: ± 3.36) on a scale of 20, which is a significant difference ( t ‐test, t = 4.07, df = 498, P < 0.001). Both groups show an improvement on the posttest compared to the pretest (paired samples t ‐test, t = 12.21/14.71, df = 257/241, P < 0.001). The improvement in the intervention group is significantly higher (ANCOVA, F = 16.59, df = 1;497, P < 0.001). It is concluded that (1) medical students studying anatomy show greater improvement between two consecutive MRTs than educational science students; (2) medical students have a higher spatial ability than educational sciences students; and (3) if a MRT is repeated there seems to be a test effect. It is concluded that spatial ability may be trained by studying anatomy. The overarching message for anatomy teachers is that a good spatial ability is beneficial for learning anatomy and learning anatomy may be beneficial for students' spatial ability. This reciprocal advantage implies that challenging students on spatial aspects of anatomical knowledge could have a twofold effect on their learning. Anat Sci Educ 6: 257–262. © 2013 American Association of Anatomists.